2016
DOI: 10.1515/ijme-2016-0005
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Network Capabilities on Firm Performance across Cultures

Abstract: The purpose of this study is to identify key factors related to network capabilities that enhance the performance of Chinese, Turkish and German firms. Chinese (n = 107), Turkish (n = 129) and German (n = 109) MBA-students completed a questionnaire, based on an earlier version developed by Kenny [2009], which included questions on the respective firm, its performance and network capabilities. The predictors of firm performance varied by country: in China "information sharing" and "trust" were important, in Tur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 69 publications
(33 reference statements)
1
8
0
Order By: Relevance
“…Where the better the network capability, the better the firm performance. This is in accordance with research by Papastamatelou et al (2016) in his research suggests that network capability affects the companies performance in several countries such as China, Turkey, and Germany. So the role of network capability on company performance is affected by culture.…”
Section: Network Capability (X3) Affects Firm Performance (Y)supporting
confidence: 92%
“…Where the better the network capability, the better the firm performance. This is in accordance with research by Papastamatelou et al (2016) in his research suggests that network capability affects the companies performance in several countries such as China, Turkey, and Germany. So the role of network capability on company performance is affected by culture.…”
Section: Network Capability (X3) Affects Firm Performance (Y)supporting
confidence: 92%
“…In general, some studies have found that network centrality (Liu et al , 2011; Kim and Lee, 2018; Das and Goswami, 2019; Wang et al , 2019), network density (Kim and Lee, 2018; Das and Goswami, 2019) and tie strength (Liu et al , 2017; Korir, 2018) have a significant and positive effect on firm performance. However, other studies have found a non-significant relationship between network centrality (Li et al , 2013), network density (AlKuaik et al , 2016) and tie strength (Li et al , 2013; Papastamatelou et al , 2016) on firm performance. Liu et al (2017) further state that the different findings are closely related to contextual or contingency factors, namely, organizational and environmental context.…”
Section: Introductionmentioning
confidence: 92%
“…Liu et al (2017) further state that the different findings are closely related to contextual or contingency factors, namely, organizational and environmental context. Organizational factors that need to be examined include firm age and size (Bhushan and Pandey, 2015; Papastamatelou et al , 2016; Corredoira and Mcdermott, 2018). Meanwhile, the environmental factor that needs to be examined in relation to the use of closed and open networks is the cultural nature inherent in entrepreneurial activities (Szkudlarek and Wu, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Networking capability is positively correlated with business performance [11]. It is also alluded that networking capability improves firm performance [18][19].…”
Section: Statement Of the Problemmentioning
confidence: 99%
“…In a longitudinal case study of manufacturing firms in New Zealand, the researcher sought to establish the role of business networks in the internationalization of manufacturing firms [29]. Further, a study seeking to determine the networking capability related factors that improved the performance of German, Chinese, and Turkish companies concluded that factors affecting performance varied across countries [18]. On the other hand, it was concluded that in cases of environmental uncertainties, network capability help improve the performance of architectural companies while managerial capability help in the real estate firm's performance [19].…”
Section: Empirical Literaturementioning
confidence: 99%